Characteristics of hydrogen production with carbon storage by CO2-rich hydrothermal alteration of olivine in the presence of Mg–Al spinel. (5th May 2020) - Wang, Jiajie; Watanabe, Noriaki; Okamoto, Atsushi; Nakamura, Kengo; Komai, Takeshi
Abstract: Artificial control of olivine alteration has potential applications for both H2 production and CO2 reduction (by mineralization and hydrogenation). To explore methods to overcome the still-constrained olivine alteration problem, olivine + spinel alteration experiments were performed with the addition of Mg–Al spinel in CO2 -rich (0.5 M NaHCO3 ) solution under hydrothermal conditions (300 °C and 10 MPa). Mg–Al spinel enhanced olivine serpentinization significantly (more than 2 times), and generation of both H2 and CO2 hydrogenation products was accelerated (up to 3 times) with ≥10 wt% Mg–Al spinel especially at the latter stage of the 72 h reaction. Mineral measurements revealed that more Al released from Mg–Al spinel was incorporated into Al-serpentine by the replacement of Fe with higher Mg–Al spinel content. Both Al and Fe incorporated into Al-serpentine were released as the reaction proceeded. Thus, H2 production was elevated with the presence of a large amount Mg–Al spinel at the latter stage of the reaction. HCO3 − played an important role in the promotion of Mg–Al spinel dissolution with the release of Al, which was stored in magnesite after being utilized. This study also suggests that the presence of Mg–Al spinel (5–20 wt%) in the starting mineral does not have significant influence on the total H2 yield from olivine alteration over the entire operation period. Highlights: Olivine alteration rate was elevated by > 2 times with Mg–Al spinel addition. By adding 20 wt% Mg–Al-spinel, H2 production rate was elevated by 1.4 times. Al released from Mg–Al spinel controls Fe(II) incorporation and oxidation. Both Al and Fe in Fe–Al-serpentine will be released as the reaction proceeds. CO2 was stored in magnesite after being utilized to promote rocks dissolution.